Atlas Based Computational Analysis of Heart Shape and Function in Congenital Heart Disease - Gilbert, Kathleen (J Cardiovasc Transl Res, 2018)
Approximately 1% of all babies are born with some form of congenital heart defect. Many serious forms of CHD can now be surgically corrected after birth, which has lead to improved survival into adulthood. However, many patients require serial monitoring to evaluate progression of heart failure and determine timing of interventions. Accurate multidimensional quantification of regional heart shape and function are required for characterizing these patients. A computational atlas of single ventricle and biventricular heart shape and function enables quantification of remodeling in terms of z-scores in relation to specific reference populations. Progression of disease can then be monitored effectively by longitudinal evaluation of z-scores. A biomechanical analysis of cardiac function in relation to population variation enables investigation of the underlying mechanisms for developing pathology. Here, we summarize recent progress in this field, with examples in single ventricle and biventricular congenital pathologies.